Influence of Polymorphisms Involved in Platelet Activation and Inflammatory Response on Aspirin-Related Upper Gastrointestinal Bleeding: A Case-Control Study - Mallah, Narmeen; Zapata-Cachafeiro, Maruxa; Aguirre, Carmelo; Ibarra-García, Eguzkiñe; Palacios–Zabalza, Itziar; Macías-García, Fernando; Domínguez-Muñoz, J. Enrique; Piñeiro-Lamas, María; Ibáñez, Luisa; Vidal, Xavier; Vendrell, Lourdes; Martin-Arias, Luis; et al. (Frontiers in Pharmacology, 2020)
Background: Despite the wide benefits of aspirin and its cost-effectiveness, aspirin prescriptions have been reduced due to idiosyncratic responses in susceptible individuals. Low-dose aspirin and single nucleotide polymorphisms (SNPs) are independently associated with increased risk of gastrointestinal hemorrhage; however, to-date, no studies investigated the SNP-aspirin interaction effect on upper gastrointestinal hemorrhage (UGIH). Therefore, we aimed to evaluate the role of 25 SNPs in multiple genes involved in platelet activation, angiogenesis and inflammatory response in aspirin-related UGIH. Methods: A multicenter, full case–control study was conducted in patients exposed and unexposed to aspirin. 326 cases diagnosed with UGIH were matched with 748 controls (1:3) by age, gender, health center and recruitment date. Only adults of European origin were included. Participants were stratified by aspirin exposure and genotype [(Aspirin(-), wild-type), (Aspirin(+), wild-type), (Aspirin(+), genetic variation), (Aspirin(-), genetic variation)]. For each SNP, the Odds Ratio of UGIH and their 95% confidence intervals were estimated in each subgroup by using the generalized linear mixed models for dependent binomial variables. SNP-aspirin interaction effect was estimated through Relative Excess Risk due to Interaction (RERI) measures. Results: We observed two categories of SNPs that might modify the risk magnitude of UGIH in aspirin consumers. Seven SNPs (rs1387180 A>G, rs2238631 T>C, rs1799964 T>C, rs5050 T>C/T>G, rs689466 T>C, rs1799983 T>A/T>G and rs7756935 C>A) were “positive modifiers” associated with an excess of risk from aspirin exposure and carrying that genetic variation (1.75 ≤ RERI ≤ 4.95). On the contrary, the following nine SNPs (rs2243086 G>T, rs1131882 G>A, rs4311994 C>T, rs10120688 G>A, rs4251961 T>C, rs3778355 G>C, rs1330344 C>T, rs5275 A>G / A>T, rs3779647(C>T) were “negative modifiers” and associated with a reduced risk in aspirin users (- 2.74 ≤ RERI ≤ - 0.95). Conclusion: This preliminary study suggests that polymorphisms in genes involved in platelets activity, angiogenesis and inflammatory response might modify the risk of aspirin-related UGIH. Further studies with larger sample size and in different populations are needed to confirm our findings. If confirmed, this might have great impact on public health, thanks to aspirin’s prophylactic properties in diseases of high incidence and severity.